Connecting the Dead and the Living: Paleoethnobotanical Evidence of Mortuary Practices and Public Ceremonies at Monte Albán - Bérubé, Éloi (My University, 2023)
The ancient Zapotec city of Monte Albán, in Oaxaca, Mexico, has been a focal point of numerous archaeological studies. It has long been presumed that grave offerings included a number of botanical elements such as maize. Nonetheless, studies of mortuary offerings and public activities have focused on architecture, ceramic assemblages, and human remains—not botanical residues. In this study, I examine botanical remains from vessels and sediment samples collected from mortuary contexts and sites of public rituals to provide novel information on those meaningful rites from three different angles. First, I examine the connections between the use of plants in temporally limited events (rituals) with medium-term phenomena (economic, political, social, etc.) taking place at Monte Albán. This study demonstrates the potential for future paleoethnobotanical studies targeting mortuary contexts and public rituals to provide novel information regarding ancient lifeways and beliefs. Second, in this study, I consider the relationship between botanical mortuary offerings and the social status of interred individuals at the Zapotec site. This allowed me to determine that there were no clear relationships between status of the deceased and plants placed plant offerings. Finally, I examine the relationship between private mortuary rituals and public rituals that took place at Monte Albán’s Main Plaza through the analysis of plant residues. This allows me to examine the key similarities and differences in those rituals that appear to have had different purposes. Indeed, as I argue in the following chapters, mortuary offerings were likely used to create a connection between the living and the dead, while public offerings allowed the inhabitants of Monte Albán to petition gods, spirits, and different supernatural entities.
Keywords: Paleoethnobotany; Mesoamerica; Oaxaca; Monte Albán